PRESUPPOSITION STRATEGIES IN DATA INTERPRETATION: CORPUS DATA ANALYSIS - Suhaimi, Mohamad Suhaizi; Yusof, Maslida (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
This study aims to describe the proses of data interpretation using presupposition strategy. Generally, presupposition refers to what the speaker assumes to be the case before making an utterance (Yule, 1996: 42). This study applies the types of presupposition proposed by Levinson (1983). Levinson had underlined nine presupposition types, which are Existential Presupposition, Factive Presupposition, Lexical Presupposition, Nonfactive Presupposition, Structural Presupposition, Counter Factual Presupposition, Iterative Presupposition, Implicative Presupposition and Temporal Presupposition. In order to emphasize the presupposition types in Malay, this research used a data corpus developed by Dewan Bahasa dan Pustaka (DBP). The results indicated that the nine presupposition types proposed by Levinson (1983) are being used in Malay sentences and speeches. Eventually, this research emphasized that the presuppositions used in communication are able to give a certain understanding to the reader or receiver especially when they get to comprehend the strategies underlined.